Spectroscopic characterization of the active FeIIIFeIII and FeIIIFeII forms of a purple acid phosphatase model system - Comba, Peter; Zajaczkowski-Fischer, Marta (Inorganic chemistry, 2012)
Two new dinucleating ligands (H3L2 and HL3), derivatives of a well-known dinucleating ligand (HL1) with two bis-picolylamine sites connected to a bridging phenolate, with hydrogen-bonding donor groups at two of the pyridine moieties were designed and synthesized. Design of these ligands suggests that they will lead to dinuclear complexes with potential to stabilize phosphoester substrates as monodentate rather than bridging ligands. We report the diferric complexes [FeIII2(H2L2)(OH)]4+ and [FeIII2(L3)(OH)(OH2)2]4+, which have been characterized by spectrophotometric titrations, UV-vis, IR, NMR, EPR, and Mössbauer spectroscopy. The phosphatase activity of the diferric systems, in addition to the partially reduced heterovalent [FeIIIFeII(L3)(OH)(OH2)2]3+ complex, has been investigated, and the complexes are shown to catalytically hydrolyze the activated phosphodiester substrate BDNPP (bis-dinitrophenylphosphate) as well as the corresponding phosphomonoester substrate DNPP (dinitrophenylphosphate). The results indicate that indeed the secondary interactions lead to an increase of the phosphatase activity and to active phosphomonoesterase catalysts. Interestingly, the heterovalent form of the HL3-based complex is more efficient than the diferric complex, and this is also discussed.